2011
DOI: 10.1021/es2007963
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of Watertype-Specific No-Effect Concentrations and Risks of Cu, Ni, and Zn

Abstract: Geographical and temporal variations in metal speciation were calculated and water-type specific sensitivities were derived for a range of aquatic species, using surveillance water chemistry data that cover almost all surface water types in The Netherlands. Biotic ligand models for Cu, Zn, and Ni were used to normalize chronic no-effect concentrations (NOEC) determined in test media toward site-specific NOEC for 372 sites sampled repeatedly over 2007-2010. Site-specific species sensitivity distributions were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 28 publications
2
52
1
Order By: Relevance
“…It is advised that the characteristics of the freshwater sites should be considered when assessing compliance with environmental quality standards (Lathouri, 2012). A similar pattern in terms of the temporal variations of the BLM parameters and risk assessment has been reported by Verschoor et al (2011) in their study in the Netherlands. In this case too, the selected surface water types covered a range of water quality parameters levels (pH 6.6-7.6; DOC 1-16 mg l −1 ; Ca 30-55 mg l −1 and Cu 1-8 μg l −1 ) but the analysis used annual averages.…”
Section: Ecotoxicitysupporting
confidence: 85%
See 1 more Smart Citation
“…It is advised that the characteristics of the freshwater sites should be considered when assessing compliance with environmental quality standards (Lathouri, 2012). A similar pattern in terms of the temporal variations of the BLM parameters and risk assessment has been reported by Verschoor et al (2011) in their study in the Netherlands. In this case too, the selected surface water types covered a range of water quality parameters levels (pH 6.6-7.6; DOC 1-16 mg l −1 ; Ca 30-55 mg l −1 and Cu 1-8 μg l −1 ) but the analysis used annual averages.…”
Section: Ecotoxicitysupporting
confidence: 85%
“…In this case too, the selected surface water types covered a range of water quality parameters levels (pH 6.6-7.6; DOC 1-16 mg l −1 ; Ca 30-55 mg l −1 and Cu 1-8 μg l −1 ) but the analysis used annual averages. Verschoor et al (2011) identified that the highest Cu risk was found from December until March and the lowest from July until October. They emphasised that seasonal risk patterns were dominated by changes in water chemistry and seasonal Cu concentration patterns, with Cu concentrations peak during winter months.…”
Section: Ecotoxicitymentioning
confidence: 99%
“…Water quality data were collected from monitoring programs covering a four-year period, thereby enabling both the geographic and the temporal (time dependent) variation analysis (Verschoor et al 2011). Water compositions varied for pH: 5.7 -8.7; DOC: 1.5 -33 mg/L; Ca: 10.7 -175 mg/L; Mg: 1.9 -42.7 mg/L; Na: 7.1 -153 mg/L.…”
Section: Application Of Pnec-pro For the Netherlandsmentioning
confidence: 99%
“…For Cd, a bioavailability correction factor based on water hardness has been suggested (e.g., [87]). Recently, Verschoor et al [93] performed a geographical and temporal analysis of TM in surface waters, and concluded that "sensitive" and "robust" waters occur, based on their physic-chemical composition. By incorporating chemical speciation of TM in the assessment of ecotoxicological risks for aquatic species, site-specific variations are made visible that remain undetected when checked with generic quality standards.…”
Section: Risks Assessment In Aquatic Environmentsmentioning
confidence: 99%